AB0038 Differential Outcome of B Cell Depletion in Patients with Anca-Associated Vasculitis (AAV) Compared to Patients with Systemic Lupus Erythematosus (SLE). (10th June 2014) - Saunders, U.; Willeke, P.; Becker, H.; Fassbinder, T.; Jung, E.; Mickholz, E.; Schlüter, B.; Jacobi, A.M.
Abstract : Background: B lymphocytes play a fundamental role in adaptive immune responses against pathogens. However, self-reactive memory B cells and long-lived plasma cells are a hard-to-hit target in patients with autoimmune diseases. Clinical trials with the B cell depleting CD20-antibody rituximab (RTX) revealed mixed results, with a benefit in patients with rheumatoid arthritis (RA) or AAV but less consistent results in patients with SLE. Objectives: To investigate the influence of B cell depletion by RTX on circulating B cells from patients with AAV and SLE. Methods: Peripheral blood samples of 12 AAV and 9 SLE patients were obtained prior and 8-12 weeks post RTX treatment and B lymphocyte subsets were analyzed by multiparameter flow cytometry. In addition, changes in immunoglobulin, free light chain (FLC), autoantibody, and BAFF serum levels were determined at both time points. Results: AAV patients displayed a significant depletion of all circulating B cell subsets 2-3 months post RTX. In contrast, 2 SLE patients had still detectable numbers of peripheral CD27 ++ CD38 ++ HLA-DR high plasmablasts, CD27 ++ CD38 ++ HLA-DR low plasma cells and CD27 + IgD – memory B cells 8-12 weeks after the RTX infusions (Table 1 ). BAFF serum levels increased by 70% in AAV (p<0.03) and 45% in SLE patients. IgA, IgG, FLC, and autoantibody levels declined but did not drop significantly during the first weeks after B cell depletion in both patient groups. However, IgM showed a significant decrease in patients with AAV (p<0.04). Conclusions: In contrast to patients with SLE, B cell depleting therapy goes along with a significant decline of all B cell subsets in patients with AAV. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2226